Effect of garlic extract coating on storage behaviour of tomato fruit - Abrol, Ghan Shyam; Kumar, Sanjeev (Journal of Postharvest Technology, 2019)
Tomato (Lycopersicon esculentum Mill.) is one of the important crop of Solanaceae family and a number of research has been conducted to extend  the shelf-life of the fruit. The present research was conducted to develop an anti-microbial coating on the fruit to extend the shelf-life of tomato fruits.  After analysis of different physico-chemical analysis garlic extract coating found to be very effective in minimising the various losses occur during the  postharvest life of fruit. The PLW was found to be 10.87% in garlic extract coating compared to 17.29% in control. However, only 10% spoilage is  observed after 21 days of storage while it was started much earlier after 15th day of storage in control fruits.
Keywords: Tomato; Garlic Extract; Quality; Spoilage; Postharvest